Analisis kesalahan berbahasa tataran ejaan pada majalah â€œMuliaâ€ edisi April 2020 - Fitriani, Aula; Mahardika, Ervy Festina; Maulana, Muhammad Yusach; Ulya, Chafit (Jurnal Genre (Bahasa, Sastra, dan Pembelajarannya), 2021)
This study aims to describe the form of the error-speaking state of spelling in the writing of magazine Mulia edition April 2020 which include: (1) errors in the use of letters; (2) the error of writing the word; (3) errors in the use of punctuation; (4) error writing element uptake; and (5) the use of the word is not raw. The object of this writing is the words, phrases, and sentences. this research is a descriptive qualitative research. Data collection techniques used in this research is documentation study. The results of the discussion showed that the overall number of the word containing the error-speaking state of spelling in the writing of magazine Mulia edition April 2020; 33 the error with the details of the 5 errors in the use of letters, 11 error writing the words, 1 usage errors punctuation, 1 error writing element uptake, 15 the use of the word is not raw.